Legal Construction of Land Rights as a Result of the Village Cash Land Exchange Process Conducted by the Village Government - Pratama, M. Yulis; Ngesti dwi Prasetyo; handiyantina, Shinta (The Islamic Education and Multiculturalism Foundation, 2024)
The focus of this legal research is to discuss the legal construction in the process of exchanging village treasury land carried out by the village government together with the village community based on statutory regulations and several scientific references in order to support the validity of the research conducted. On the island of Java, village treasury land or what is usually known as bengkok land should be productive land so that it can provide added value and become a source of income for the village head and his apparatus, but in reality, not all village-owned land is productive land so that it makes the village government experience a decrease in production due to less productive land. The problem also arises when the village treasury land in the form of a yard is occupied by the village community, because it has been settled for a long time, the community wants legal status to the land they occupy by buying the village treasury land through the exchange process, the sale-purchase agreement occurs between the surrounding community and the village government As a form of follow-up to the sale-purchase process that has been carried out between the village government and the community, there is a release of the status of land rights. in this case there is legal uncertainty where people who have paid off the land have not been able to get a certificate for the land they have paid for. The research method used is Normative Juridical research based on laws and regulations which are then reviewed using applicable legal theories, concepts and principles so that it is expected to know and find the facts and data needed. Then briefly the research results show that 1. The status of land rights on village treasury land is included in the status of the right of use, this refers to the definition of the right of use stipulated in Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles Article 41 which states that the right of use is the right to use and/or collect products from land directly controlled by the State or land owned by others, which gives the authority and obligations specified in the decision to grant it by the official authorized to grant it or in the agreement with the owner of the land, which is not a lease agreement or land processing agreement, everything as long as it does not conflict with the spirit and provisions of this Law.